Governing the Information Ecosystem: Southeast Asia's Fight Against Political Deceit. (3rd September 2019) - Goh, Shawn; Soon, Carol
Abstract : Political upheavals like the 2016 United States Presidential election have thrown political deceit into the global spotlight. Political deceit can cause varying degrees of harm—from exacerbating existing social fault lines to potentially undermining democratic processes and effective governance. Thus, governments around the world are responding seriously to combat the scourge. In Southeast Asia, governments have recognized the need to tackle the problem in collaboration with one another. By focusing on the developments in Southeast Asia and using a framework comprising four governance capabilities (viz., reflexivity; responsiveness; resilience; and revitalizing) to manage a wicked problem like political deceit, this article argues that a multistakeholder approach is more effective and sustainable in fighting political deceit than is a top-down government-centric one due to three reasons. First, with trust in institutions at a global lull, governments that face a trust deficit may see poor results if they rely solely on legislation or government-led fact checking. Second, the effectiveness of government interventions may be circumscribed by psychological biases that underpin how people process political deceit. Third, governments should partner with nonstate actors, who also play a critical role in tackling this wicked problem, and bring diverse stakeholders together to leverage collaborative advantage.